POLA PENYEBARAN ANGGREK Dendrobium sp DI KAWASAN TAMAN NASIONAL LORE LINDU (Studi Kasus : Desa Mataue Kecamatan Kulawi Kabupaten Sigi Sulawesi Tengah) - Tikuallo, Novita Resky; Mallombasang, Sri Ningsih; Labiro, Elhayat (Jurnal Warta Rimba, 2020)
Dendrobium orchid is an orchid that has an epiphytic way of life. In Mataue There are several types of orchids including Dendrodium sp. orchids which are the favorite one for the  Villager.But the spread pattern of the orchid still unknown, Yet the information about the Pattern of Spread of orchids is important for conservation’s efforts or orchid cultivation. This study aims to determine the pattern of the spread of orchids Dendrobium sp. in Lore Lindu National Park area, Mataue Village, Kulawi District, Sigi Regency, Central Sulawesi. This research was conducted in August until September 2018. The method used in this study was carried out with using an analyzing double plot method  vegetation that placed intentionally (Purposive Sampling) as many as 7 plots with each size of 20m x 20m. The results of the study showed that from 7 observation plots found 113 species of orchids Dendrobium sp is Dendrobium macrophyllum as many as 58 individuals and Dendrobium 55 individuals of the Dendrobium crumenatum. The patterns of the spread of  Dendrobium sp. orchids were found at an elevation of 583-836 meters above sea level (m above the surface of the sea) it grows with a spread pattern grouping with the Morisita Index (Iδ) is in the category of the value Ip> 0 (more than zero). Dendrobium macrophyllum has an Ip value of 0.1122 and Dendrobium crumenatum has a value of Ip 0.5810.Keywords : Dendrobium sp. Orchid, Spread Pattern, Lore Lindu National Park